(untitled) (Journal of Contemporary Educational Policies and Practices, 2022)
The family is regarded as the essential institution since it is the first place where young children are acculturated, learn values, and develop a sense of belonging. Childhood plays a significant role in determining a person’s life path. For most people, their parents are their most important teachers. Even after childhood, family ties continue to have a significant educational impact. People engage in family education not only as children but also as parents and grandparents. The family is the first significant educational institution in the context of other community groups. Thus, the context of family influences the education and learning process of children directly and indirectly. This article concentrates on how family context may affect the learning process of family members. It also explains how the family socio-economic status role in shaping children’s learning process, and the way relationship between parent-school and family members within family institution affects schooling.